# Id like you guys to please solve question number 6. Thanks!

Sayam
49 Points
6 years ago
as cot$\theta$-cot3$\theta$
=cos$\theta$/sin$\theta$-cos3$\theta$/sin3$\theta$
=2 cos$\theta$sin3$\theta$-2cos3$\theta$sin$\theta$/2sin$\theta$sin3$\theta$  …. taking LCM
=sin4$\theta$+sin2$\theta$-sin4$\theta$+sin2$\theta$/2sin3$\theta$sin$\theta$
=2cos$\theta$cosec3$\theta$
Hopes this clears your doubt. Thanks
Sarasij Basu Mallick
33 Points
6 years ago
$\theta$-cot3 $\theta$cot
=(cos$\theta$ /sin$\theta$ )-(cos3$\theta$ /sin3$\theta$ )
=((sin3$\theta$ cos$\theta$ -cos3$\theta$ sin$\theta$ )/(sin$\theta$ sin3$\theta$ ))
=((sin2$\theta$)/(sin$\theta$sin3$\theta$ ))
=((2sin$\theta$ cos$\theta$ )/(sin$\theta$ sin3$\theta$ ))
=2cos$\theta$ cosec3$\theta$ --------------c

Sarasij Basu Mallick
33 Points
6 years ago
---------SORRY SORRY SOMETHING WENT WRONG IN TYPING----------
cot$\theta$-cot3$\theta$
=(cos$\theta$ /sin$\theta$ )-(cos3$\theta$ /sin3$\theta$ )
=((sin3$\theta$ cos$\theta$ -cos3$\theta$ sin$\theta$ )/(sin$\theta$ sin3$\theta$ ))
=((sin2$\theta$)/(sin$\theta$sin3$\theta$ ))
=((2sin$\theta$ cos$\theta$ )/(sin$\theta$ sin3$\theta$ ))
=2cos$\theta$ cosec3$\theta$ --------------c